Correction: Díaz Ferreyra, N.E., et al. Preventative Nudges: Introducing Risk Cues for Supporting Online Self-Disclosure Decisions. Information 2020, 11, 399 - Nicolás E. Díaz Ferreyra; Tobias Kroll; Esma Aïmeur; Stefan Stieglitz; Maritta Heisel (Information, 2020)
After publication of the research paper [...]